Changing Social Behavior in Drinking Water Projects: A Revision of Water Supply Scheme in Western Nepal (Nepalese Journal of Development and Rural Studies, 2017)
This paper explored changing social behaviors of the service beneficiaries in drinking water supply schemes. The study included five most accepted types of water schemes like; overhead tank system, shallow tube well system, gravity system, rainwater harvesting and water lifting system. Intrinsic case study methodology was applied to evaluate eleven drinking water project of western region of the country. Field observation, focus group discussion, and key informant interview methods were deployed during collecting information. This study found that all the drinking water schemes are running presently with big social and cultural issues. Beneficiaries are changing their behaviour while getting drinking water services offering by government and non-government mechanism. As so far, for natural and effective use of drinking water schemes it is inevitable to change social stigma and cultural attitude of the local people. Finally, this study reveals the importance of social analysis during drinking water project formulation stage so that issues of changing social behaviour of the beneficiaries can be addressed. Nepalese Journal of Development and Rural StudiesVol. 14 (Joint issue) (1&2), 2017, Page: 80-85